Water in Deep Eutectic Solvents: New Insights From Inelastic Neutron Scattering Spectroscopy - Nolasco, Mariela M.; Pedro, Sónia N.; Vilela, Carla; Vaz, Pedro D.; Ribeiro-Claro, Paulo; Rudić, Svemir; Parker, Stewart F.; Freire, Carmen S.R.; Freire, Mara G.; Silvestre, Armando J. D. (Frontiers in Physics, 2022)
The effect of water on the physicochemical properties of deep eutectic solvents (DES) is a trending research topic. In this work, inelastic neutron scattering (INS) spectroscopy, was used to probe intermolecular interactions in the water-deep eutectic solvent mixtures for the cases of choline chloride (the hydrogen bond acceptor) and three different hydrogen bond donors, with different degrees of acidity: urea, glycerol and lactic acid. It was found that quenching samples in liquid nitrogen is a procedure that may retain the liquid phase morphology of DES at the low temperatures required by INS spectroscopy. The three studied systems share the preference of water molecules to bind to chloride anion, as predicted by numerous molecular dynamics simulations. Despite this similarity, the three systems present several distinct INS features upon water addition that are related to their unique properties and structure at the molecular level. In the choline chloride:urea system, water molecules promote a strengthening of hydrogen bonds with the NH and OH donors, while for the choline chloride:lactic acid system INS probed the existence of solvated DES clusters instead of specifically interfering water molecules. This study takes advantage from the unique capabilities of INS and paves the way for future studies in these systems.